Fraud Auditing Law Implications in the Case of Jiwasraya Insurance in Indonesia - Sari, Ariella Gitta (International Journal of Business, Economics and Management, 2020)
The Jiwasraya case is a fraud auditing legal case that has taken a lot of public attention and is particularly influential on capital market investors. The purpose of this study is to find out the legal implications of the Limited Company case and preventive measures that can be taken so that similar cases are no longer repeated. By using normative and empirical research methods, the study presents the conclusions that it is very important training in fraud detection and prevention especially for internal auditors in the Limited Company. In this case, being cautious in investing to avoid "fried" shares is an important lesson for other companies. Based on the Jiwasraya case empirical study where only recently detected cases of corporate asset fraud revealed the facts about the lack of a comprehensive understanding of fraud auditing, technology implementation, and corporate management mechanisms that are not in accordance with Good Corporate Governance in the corporate body.